The Concept of Aether in Classical Electrodynamics and Einstein's Relativity - Ličer, Matjaž (Filozofski vestnik, 2013)
The paper sketches the impact the concept of aether had on the historical development of relativistic physics. It depicts how and why the concept of aether was at the core of a seeming contradiction between the Galilean principle of relativity and the law of the constancy of the speed of light, which implied a fundamental discord between classical electrodynamics and Newtonian mechanics, and was a major topic throughout 19th century physics. We note some of the consequences of Einstein’s formulation of special relativity, which represented a synthesis of both mentioned theories within one common theoretical framework. It also led Einstein to ban the notion of aether from physics. The paper describes Einstein’s development from special to general relativity and shows how the latter eventually influenced his reintroduction of the concept of relativistic aether to accentuate the dynamic properties of general relativistic spacetime.